Saffron : science, technology and health - Koocheki, A.; Khajeh-Hosseini, Mohammad (Woodhead Publishing in food science, technology, and nutrition., 2020)
Saffron: Science, Technology and Health summarizes the scientific, technical and health aspects of this crop. Saffron possesses unique agronomical, ecological, social and physiological characteristics. And, there are various chemical components present in saffron, including carbohydrates, minerals, vitamins, color pigment, aromatic and flavoring agents. Saffron has a long history of use in traditional medicine, and in recent years, the application of saffron in the medical industry as a cancer curing and antidepressant agent has brought more attention. There is also a growing trend of saffron use in the conventional food industry, including saffron desserts, cream, butter, beverages, powders, cake mixes and soups. Intended for nutrition scientists and scientists and technologists working in the areas of food, agriculture, new product development and pharmacology.